Managerial and Environmental Factors on the Risk of Loan Default in Micro-Enterprises - Agus Khairudin Ahmadi; Eliada Herwiiyanti (International Journal of Business, Law, and Education, 2026)
In Indonesia, micro-enterprises play a strategic role in the national economy. In fact, the sustainability of micro-enterprises often faces challenges due to the high risk of loan default. This study aims to examine the role of managerial and environmental factors as two key determinants of the risk of loan default in micro-enterprises. A narrative literature review method was used to analyze eight scientific articles published between 2016 and 2025 that were relevant to the research topic. The study found that managerial factors such as financial literacy, business planning, and cash flow management influence the ability of micro-entrepreneurs to repay loans. Meanwhile, environmental factors such as macroeconomic conditions, government policies, and social dynamics can strengthen or weaken the financial stability of micro-enterprises. The implications of this research demonstrate the importance of strengthening managerial capacity and creating a conducive business environment as key strategies to reduce the risk of loan default